DEVELOPMENT OF IPA LEARNING MODULE BASED ON STEM TO GROW HOTS VIBRATION FOR SMP - Fopi Angraini; Ahmad Walid; Edi Ansyah; Adli Ikhsan (Jurnal Muara Pendidikan, 2022)
The aim of the study was to develop STEM-based IPA modules to Grow HOTS of Vibration, Wave and Sound Materials For Grade VIII Junior Students. The method used in this study uses the Thiagarajan 4-D model which consists of (4) four stages namely Define (Defining), Design (Design), Develop (Development), Disseminate (Dissemination). The research was conducted only up to the stage of small-scale trials. The instrument used is a validation questionnaire to the feasibility of the module and the student's response to stem-based IPA modules to grow HOTS of vibration, wave and sound material. The subjects in the study were 3 lecturers of the Bengkulu State Islamic Institute. The conclusion of this research is that the module developed has been feasible, and practically used as teaching materials in supporting the teaching and learning process on vibration, wave and sound materials in fostering the hots ability of junior high school students for class VIII.